The right to not be subjected to torture: status quaestionis - García Cívico, Jesús (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
This work analyzed the current situation of the right not to be tortured. It starts with the idea, reflected in the highest legal instruments, that this is absolute and admits no exception. The right not to be tortured is not just one more in the catalog of human rights but a fundamental element in the origin, purpose and rationality of them. An examination of recent cases, collective social perceptions, political and academic debates allows both shed light on the current state of the traditional problems related to their effectiveness as getting a general idea about the situation of the (worrying) evolution of this right. The conclusion is that traditional mechanisms of effectiveness must be strengthened from three wide perspectives: moral, legal, and, mainly, socio-political. doi: https://doi.org/10.20318/universitas.2017.3542